Government Strategies to Reduce Stunting Through Specific and Sensitive Nutrition Interventions in Tarakan City, North Kalimantan Province - Mulka, Sry Reski; Prameswari, Tryecia (Department of Government Studies, Universitas Syiah Kuala, 2025)
Stunting is a chronic health problem that affects the growth and development of children and is one of the highest causes of death in children in Indonesia. To address this, the government issued Presidential Regulation Number 72 of 2021 concerning the acceleration of stunting reduction. This policy was followed up by the Tarakan City Government through Mayor Regulation Number 1 of 2024, in line with the vision and mission of the regional head which emphasizes improving the degree of public health. This study aims to evaluate the effectiveness of the strategies implemented by the Tarakan City Government in reducing stunting rates and their impact on the community. The research was conducted using qualitative methods through in-depth interviews with purposively selected informants, as well as document analysis and secondary data from official reports and other relevant sources. The results showed that the strategy was effective, received a positive response from the community, and showed a downward trend in stunting rates. Policy implementation also shows inter-agency collaboration in accordance with the duties and functions of each regional apparatus, supporting the achievement of national targets.